"CARE" in social media: perceptions of reputation in the healthcare sector. Issue 2 (5th May 2021) - Chaudhri, Vidhi; Oomen, Tessa; Pridmore, Jason; Joon, Alexandra
Abstract : Purpose: Guided by the growing importance of social-mediated organisational communication, this study examines how communication professionals within healthcare organisations perceive and respond to the reputation impacts of social media on the organisation's reputation. Although the healthcare sector finds itself in the midst of a (continually) transforming landscape characterised by large amounts of digital health (mis)information and an empowered "patient-as-consumer", little is known about how professionals in this sector understand the changes and respond to them. Moreover, much extant scholarship on the topic is published in specialised health or medical journals and does not explicitly address the communication implications for healthcare organisations. Design/methodology/approach: In-depth semi-structured interviews were conducted with communication professionals responsible for social media across eight hospitals in the Netherlands. The sample included two participants working as communication consultants/social media advisors for healthcare organisations. In all, 15 interviews were conducted. Findings: Building on interviewee perspectives, the authors advance the CARE (Control, Access(ability), Responsive(ness) and Engagement) model of social-mediated communication, highlighting the dualistic characteristics of each dimension. This model is built upon a careful analysis of healthcare professional responses. In an always-on environment, understanding and managing the tensions within the authors' model may be decisive to the reputation implications of social media use. Originality/value: Understanding the tensions within each dimension lends a more nuanced perspective on the potential impact(s) of social media as experienced by professionals in the field. In shifting away from a binary, either/or approach, the paper contributes to explicating the complexities of a pervasive phenomenon (i.e. social-mediated communication) and its multifaceted impacts on the healthcare sector.